Pre-symptomatic prediction of morbitidies in preterm infants with patent ductus arteriosus by targeted neonatal echocardiography and brain-type natriuretic peptide - Yasser Elsayed; Mary Seshia; Reeni Soni; Ilan Buffo; Ronald J. Baier; Patrick J. McNamara; Shyamala Dakshinamurti (Journal of Pediatric and Neonatal Individualized Medicine, 2016)
Objectives: Our objective was to compare patent ductus arteriosus (PDA) diameter, PDA score and brain-type natriuretic peptide (BNP) measurements at 48-72 hours of life, for prediction of neonatal morbidities. We hypothesized that use of a PDA score with BNP, may improve pre-symptomatic prediction of PDAs associated with adverse outcomes.